Биоэкологические особенности и структура растений Zingeria biebersteiniana (Claus) P. Smirn. (Poaceae) - Никифоров, А.Р.; Корженевский, В.В. (Український ботанічний журнал, 2010)
Нашей целью было изучение особенностей онтогенеза и морфологической
структуры растений. Предварительным этапом работы была интродукция Z. bieber
steiniana в приморский пояс Южного Крыма (Никитский ботанический сад). Zingeria biebersteiniana (Claus) P. Smirn. (Poaceae) має полідиз’юнктивний ареал, який потенційно охоплює локальні ландшафти озер, річок та інших водойм південного сухого степу Північного Причорномор’я. Це озимий однорічник, квітуючий у травні. Морфоструктура Z. biebersteiniana формується з головного та бічних пагонів. Головний пагін складається з кількох структурно-функціональних зон: відновлення, гальмування, збагачення. Синфлорес ценція виду належить до політелічного типу. Species Zingeria biebersteiniana (Claus) P. Smirn. (Poaceae) has a polydisjunctive range which includes the landscapes of lakes, rivers and other pools drying in summer in southern dry steppe on the territory of Priazovye and Steppe Crimea. The plant belongs to winter annuals, summer flowering ep he mers. Morphological structure of plant consists of main and side shoots. The main shoot of Z. biebersteiniana consists of structural and functional zones: regeneration, inhibition, enrichment. Synflorescence of Z. biebersteiniana belongs to synflorescense of politely type.